TINGKAT KECEMASAN WASIT SAAT MEMIMPIN PERTANDINGAN SEPAK BOLA DI KABUPATEN INDRAGIRI HULU - Mardian, Aldi; Vai, Aref; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The issue addressed in this study is that some referees in the Indragiri Hulu Regency Football Association still experience doubts due to fear of failure in officiating matches, fear of declining performance quality, fear of injury or other incidents, and concerns about physical condition affecting their ability to complete their duties. Additionally, referees reported experiencing anxiety during football matches due to fear of physical or non-physical aggression from spectators and players. This study aims to determine the level of anxiety experienced by referees while officiating football matches in Indragiri Hulu Regency. The research employed a descriptive method. The population in this study consisted of all licensed C1, C2, and C3 football referees in Indragiri Hulu Regency, totaling 21 individuals. The sampling technique used was total sampling, resulting in 21 respondents. The research instrument used was a questionnaire with a Likert scale. Data analysis was conducted using descriptive quantitative analysis in the form of percentage values. Based on the results, it can be concluded that the overall level of referee anxiety while officiating football matches in Indragiri Hulu Regency falls into the very low category, with an average percentage of 54.78%, which is below the 55% threshold. Keywords: Referee anxiety level, football